Australia : Financial Sector Assessment Program; Technical Note; Investor Protection, Disclosure, and Financial Literacy. (IMF Staff Country Reports; Country Report ;, 2006)
This study reviews selected issues on investor protection and corporate governance in Australia, and concludes that the corporate governance framework for Australian-listed companies is largely healthy and dynamic. Shareholder activism is an important element of corporate governance because it promotes compliance and implementation of disclosure and corporate governance obligations. The legislative and regulatory framework in Australia includes disclosure requirements that meet or exceed the requirements that exist in many other countries. Disclosure and transparency are key components of the OECD Principles of Corporate Governance.